Thermal response of chalcogenide microsphere resonators - Ahmad, Harith; Aryanfar, Iman; Lim, Kok Sing; Chong, Wu Yi; Harun, Sulaiman Wadi (Kvantovaya Elektronika and Turpion Ltd, 2012)
A chalcogenide microsphere resonator (CMR) used for temperature sensing is proposed and demonstrated. The CMR is fabricated using a simple technique of heating chalcogenide glass and allowing the molten glass to form a microsphere on the waist of a tapered silica fibre. The thermal responses of the CMR is investigated and compared to that of a single-mode-fibre (SMF) based microsphere resonator. It is observed that the CMR sensitivity to ambient temperature changes is 8 times higher than that of the SMF-based microsphere resonator. Heating the chalcogenide microsphere with a laser beam periodically turned on and off shows periodic shifts in the transmission spectrum of the resonator. By injecting an intensity-modulated cw signal through the resonator a thermal relaxation time of 55 ms is estimated.